A Study on the Application of WhatsApp Business Features in Operational Outreach with reference to Mahindra & Mahindra Nagpur - Dhaneshwar Bhanarkar, Abhishek; Tekade, Atul B. (Journal of Neonatal Surgery, 2025)
The integration of digital tools in business operations has transformed communication practices, offering innovative solutions for outreach and engagement. WhatsApp Business, with its versatile features, has emerged as a significant platform for operational outreach in organizations. This study explores the application and impact of WhatsApp Business features in enhancing operational efficiency at Mahindra & Mahindra in Nagpur. By leveraging tools such as automated messaging, labels, and catalogue sharing, the platform facilitates seamless interaction with customers and stakeholders. The research employs a mixed-method approach, incorporating both qualitative and quantitative data collected through surveys and interviews with key personnel and end-users. Key findings indicate that WhatsApp Business enhances communication speed, personalizes customer interactions, and reduces operational bottlenecks. However, challenges such as data privacy concerns and limitations in feature scalability are also noted. The study underscores the need for strategic integration of digital communication tools, highlighting their role in improving customer relationship management and operational outreach. Insights from this research can guide organizations in optimizing WhatsApp Business features to achieve better connectivity and operational efficiency.